Sucrose reduction in white layer cake - Mohammad, Tasnim (Kansas State University, 2014)
The prevalence of diabetes along with the perceived impact of sugar on health in general has increased the demand for reduced-sugar and sugar-free baked products. Cakes typically contain large quantities of sucrose which affects not only flavor but also color, volume, and texture. This study evaluated the effect of replacing sucrose in white layer cakes with polydextrose and two artificial sweeteners: sucralose and stevia extract. White layer cakes were made using AACCI Method 10-90.01. Batter properties were evaluated by measuring specific gravity. Volume index was measured using a cake template (AACCI Method 10-91.01). Slice area, number of cells, number of holes, and wall thickness of the crumb were calculated and recorded using C-Cell Cake Imaging system. Control batter made with 135% water had a specific gravity of 0.90 g/cc and a cake volume index of 112. The cakes had a nicely golden brown, shiny surface. The crumb grain was fine with an even cell distribution. Optimum water level and baking time were obtained for each cake variation. Although replacing sucrose with polydextrose had no significant effect on specific gravity (p>0.05), a 25% replacement resulted in a cake with a volume index of 110, 50% with an index of 105, 75% with an index of 103, and 100% with an index of 97. The crumb grain was similar to the control cake. Adding sucralose and stevia yielded similar results, where lower volumes were recorded as polydextrose and sucralose/stevia were increased in the cake formula. Complete replacement of sucrose with polydextrose and sucralose or polydextrose and stevia produced an acceptable volume of cake. The number of holes and wall thickness of the crumb was not significantly different in any cake variation. Therefore, polydextrose and both sucralose and stevia are suitable as sucrose replacers in cakes. Key indexing terms: cakes, polydextrose, stevia, sucralose.
Keywords: Cakes; Polydextrose; Stevia; Sucralose; Food Science (0359)